Dielectric response of BaTiO3 electronic states under AC fields via microsecond time-resolved X-ray absorption spectroscopy. (1st April 2021) - Kato, S.; Nakajima, N.; Yasui, S.; Yasuhara, S.; Fu, D.; Adachi, J.; Nitani, H.; Takeichi, Y.; Anspoks, A.
Graphical abstract: Abstract: For the first time, the dielectric response of a BaTiO 3 thin film under an AC electric field is investigated using microsecond time-resolved X-ray absorption spectroscopy at the Ti K-edge in order to clarify correlated contributions of each constituent atom on the electronic states. Intensities of the pre-edge e g peak and shoulder structure just below the main edge increase with an increase in the amplitude of the applied electric field, whereas that of the main peak decreases in an opposite manner. Based on the multiple scattering theory, the increase and decrease of the e g and main peaks are simulated for different Ti off-center displacements. Our results indicate that these spectral features reflect the inter- and intra-atomic hybridization of Ti 3 d with O 2 p and Ti 4 p, respectively. In contrast, the shoulder structure is not affected by changes in the Ti off-center displacement but is susceptible to the effect of the corner site Ba ions. This is the first experimental verification of electronic contribution of Ba to polarization reversal.